2001
DOI: 10.1093/jjco/hye062
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Autologous Tumor-specific T Cell Clones From a Patient With Adenosquamous Carcinoma of the Lung

Abstract: These results are the first demonstration of a successful induction of AT-specific T cell clones from a patient with lung adenosquamous carcinoma. It may therefore supply a possible way to apply specific immunotherapy to this type of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…One week after the third stimulation, the RLNLs were harvested, washed, and tested for their CTL activity. To establish CTL clones from CTL lines, a limiting dilution method was done as reported previously (20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One week after the third stimulation, the RLNLs were harvested, washed, and tested for their CTL activity. To establish CTL clones from CTL lines, a limiting dilution method was done as reported previously (20).…”
Section: Methodsmentioning
confidence: 99%
“…16). In a blocking assay, one fourth of diluted culture supernatant of hybridomas was added to the coculture of CTLs and tumor cells (20).…”
Section: Methodsmentioning
confidence: 99%
“…We reported that tumor-specific CTL clones could be induced from regional lymph node lymphocytes in lung cancer patients (9)(10)(11)(12)(13). In this study, we identified a new cancer/germline antigen recognized by CTL using cDNA expression cloning method.…”
Section: Introductionmentioning
confidence: 98%
“…To establish T-cell clones, a limited dilution method was performed on the bulk CTL line, as reported previously. 31 …”
Section: Induction Of Bulk Ctls and Generation Of Ctl Clonesmentioning
confidence: 99%
“…In the blocking assay, a one-quarterdiluted culture supernatant of hybridomas was added to the coculture of CTLs and tumor cells, as reported previously. 31,33 …”
Section: Measurement Of Interferon ␥ Production By Ctlsmentioning
confidence: 99%